2000
DOI: 10.1046/j.1365-2265.2000.01108.x
|View full text |Cite
|
Sign up to set email alerts
|

Sustained reduction in circulating cholesterol in adult hypopituitary patients given low dose titrated growth hormone replacement therapy: a two year study

Abstract: The effect of GH on lowering total and low density lipoprotein-cholesterol is more prominent in patients with higher pretreatment cholesterol levels and is evident even in patients receiving other lipid-lowering medication. A modest increment in mean fasting glucose (within the reference range) and mean glycated haemoglobin persisted throughout the study. One patient developed diabetes mellitus. A GH replacement regimen using low dose and careful titration to avoid elevated IGF-I levels and adverse effects is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
48
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 34 publications
(62 reference statements)
11
48
2
1
Order By: Relevance
“…This contrasts with a number of previous findings suggesting that GH replacement has different effects in different subgroups, such as age of onset (43) or gender (50). The homogeneity of therapeutic effects of GH has been shown before for elderly patients (51) and the additive effect of GH, apart from lipid-lowering drugs has also been demonstrated (52). There was a clear trend of the effects of GH treatment to be greater after 2 years than after 1 year and be most marked in patients with the most pronounced hypercholesterolaemia at baseline.…”
Section: Discussioncontrasting
confidence: 55%
“…This contrasts with a number of previous findings suggesting that GH replacement has different effects in different subgroups, such as age of onset (43) or gender (50). The homogeneity of therapeutic effects of GH has been shown before for elderly patients (51) and the additive effect of GH, apart from lipid-lowering drugs has also been demonstrated (52). There was a clear trend of the effects of GH treatment to be greater after 2 years than after 1 year and be most marked in patients with the most pronounced hypercholesterolaemia at baseline.…”
Section: Discussioncontrasting
confidence: 55%
“…In placebocontrolled studies, with a duration ranging from 1 week to 18 months, rhGH treatment was beneficial for lean and fat body mass, total and high-density lipoprotein (HDL) cholesterol levels and diastolic blood pressure (DBP), whereas rhGH negatively influenced plasma glucose and insulin levels (1). Long-term studies have revealed an increase in HDL cholesterol (2)(3)(4) and fasting glucose levels (3)(4)(5)(6), and a decrease in triglyceride (TG) levels (3,7). Systolic blood pressure (SBP) remained unchanged (3,7,8), whereas DBP decreased only in one study (8).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas patients with adrenal insufficiency may develop severe symptoms, GH deficiency (GHD) in adults typically presents with subtle signs. GHD may be clinically characterized by changes in body composition, impaired psychological well-being, reduction in bone mineral density, and metabolic alterations in lipids and insulin resistance, which GH replacement reverses (1)(2)(3). Under these circumstances, the diagnosis in a suspected patient is purely biochemical, based on an insufficient GH peak response in one or two stimulation tests, depending on the number of other pituitary hormone deficiencies (4).…”
Section: Introductionmentioning
confidence: 99%